Art first : Photo. (Paris : Art first, 1983)
Ommer, Uwe ; Vidal, Bernard ; Scialom, Jean-Marc ; Molina, Antonio ; Bernad, Antoni ; Jeroni ; Miquel, Miguel Martinez Ramon ; Miserachs, Xavier ; Eguiguren, Hermanos ; Reichel, Jean-Noel ; Malke, Michel ; et al.
Art First is the first international network which enables an artist to be represented and commercialized simultaneously in different countries by the same entity.
kunstcatalogus